Análisis jurídico y comparado de la adecuación del tipo penal del delito de femicidio en grado de tentativa y la reparación integral de la víctima. - Carpio Jimenez, Jocelyne del Cisne (2023)
The present degree thesis is entitled: "Legal and comparative analysis of the adequacy of the criminal offence of attempted femicide and the comprehensive reparation of the victim", with a focus on the crime of the attempt of femicide, this being the most serious violent attack against women, so that for femicide to be configured as a criminal offence there must be full consummation of the act, otherwise the act will be classified as an attempt. However, there is perplexity in the classification of the criminal type in procedural practice by the administrators of justice, so it is necessary to establish a guideline that regulates the procedure of the criminal act, in order to establish a correct application of the attempt valued from the intentionality of the author and the reproachability of his conduct. In view of the above, the problem of the misapplication of the criminal offence of attempted femicide in a process of violence with risk factors for the victim is a significant legal problem, given that the State and the jurisdictional bodies have the duty to protect and protect the rights of women and in this way safeguard the right to legal certainty. Furthermore, the analysis of a sustainable integral reparation for the victim and the respect of their rights and constitutional guarantees that protect the full exercise of these rights during the process also arises. In the development of the thesis, materials and methods were applied that have allowed the development of the present investigation, in the same way, interviews and surveys were carried out with legal professionals, obtaining results that have served to propose a legal proposal for the reform of the law of the Organic Integral Penal Code, with the aim of correctly applying the criminal type of attempted femicide and thus sustaining a fair process and a comprehensive reparation for the victim.